2002
DOI: 10.1017/s1047951102000975
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support via percutaneous endoscopic gastrostomy in children with cardiac disease experiencing difficulties with feeding

Abstract: Adequate nutrition is crucial to the management of children and infants with cardiac disease. Difficulties with feeding are extremely common, and maintaining an adequate caloric intake, in order to achieve sustained growth, is often not possible without nutritional support. We retrospectively reviewed our experience between 1995 and 1999 in treating 37 children with cardiac disease who underwent percutaneous endoscopic construction of a gastrostomy to augment nutritional needs. We stratified the patients into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…There exists very little previous data examining enteral feeding patterns and outcomes among patients with congenital heart disease, a population in which malnutrition has long been recognized to be common [5,6] . Schwalbe-Terilli et al [7] evaluated the caloric intake of 100 neonates receiving enteral nutrition after cardiac surgery, 52 with biventricular cardiac defects and 48 with a functional single ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists very little previous data examining enteral feeding patterns and outcomes among patients with congenital heart disease, a population in which malnutrition has long been recognized to be common [5,6] . Schwalbe-Terilli et al [7] evaluated the caloric intake of 100 neonates receiving enteral nutrition after cardiac surgery, 52 with biventricular cardiac defects and 48 with a functional single ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…The types of surgical repair included Norwood procedure in 14 infants (20.9%), hybrid procedure in 4 (6%), TAPVR repair in 9 cases (13.4%) and coarctation/interrupted aortic arch repair in 8 infants (11.9%). A teratology repair was performed in 3 infants (4.5%) and a modified BT shunt placed in 15 infants (22.4%) with tetralogy physiology [6] , hypoplastic right heart [5] , transposition of great vessels [2] , Ebstein anomaly [1] and tricuspid atresia [1] . Truncus repair was done in 6 (9%), arterial switch procedure in 4 infants (6%) and systemic to pulmonary artery shunts in 2 cases (3%), pulmonary artery banding and heart transplantation in 1 case each (1.5%).…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…Studies have shown that tube feeding can be beneficial to children with a variety of conditions such as chronic renal failure, liver disease, or heart disease, where calorie intake might otherwise be inadequate and lead to malnutrition [1][2][3]. Other children may have structural abnormalities of the digestive tract or absorption problems, which require tube feeding and/or total parenteral nutrition.…”
mentioning
confidence: 99%
“…It could also be shown that weaning is harder if the patients are older (6% per month). Our cardiological ill group in mean is older than the others and so we believe that overfeeding before surgery [5] is the main cause for better weaning…”
mentioning
confidence: 89%